Alternative Views on Psychopathy: From Pathology to Adaptive Life Strategy - Petrović, Boban; Međedović, Janko (Zbornik Instituta za kriminološka i sociološka istraživanja, 2012)
Psychopathy is a construct that has attracted the attention of practitioners and researchers for more than 200 years. A large number of studies of psychopathy have been carried out to date, particularly in the last 20-odd years, making a significant contribution to the understanding of this phenomenon. This paper analyzes different theoretical viewpoints of understanding psychopathy, from a clinical context from which it sprang, and in which it is almost exclusively seen as a form of pathological behavior, towards an attempt to understand psychopathy as an extreme manifestation of basic personality traits, and finally, a view of psychopathy as an adaptive life history strategy. Arguments are provided in favor of the latter viewpoint.